Territorial song in the Oriental Magpie-Robin Copsychus saularis in suburban areas of Kota Samarahan, Sarawak - Zahran Mansor; Dency Flenny Augustine Gawin (Indonesian Ornithologists’ Union, 2020)
Despite its reputation for unique and melodious vocalisations, the Oriental Magpie-Robin Copsychus saularis remains remarkably under-studied in Borneo. We undertook an examination of the territorial song of this species at the Universiti Malaysia Sarawak campus and Kota Samarahan, Sarawak, to learn more about its structure, repertoire size and physical characteristics. Throughout the breeding season, males started to sing intensely usually half an hour before sunrise until 09:00 or 10:00 hrs. Fifty minutes of song were collected from each of five colour-ringed breeding males. From the total of 2,198 phrases, 112 different phrase types were identified. Spectrograms revealed that most singing episodes consist of a repeated phrase, many of which vary by including dissimilar syllables. We confirmed that the purpose of males singing was to secure and maintain their territories, as males aggressively responded to playback near their nesting sites by increasing their singing rates. The female’s song seems to initiate male territorial singing during the entire breeding season.